OPTIMALISASI PERAN DIREKTORAT PENGAMANAN OBJEK VITAL POLDA SUMBAR DALAM PENANGGULANGAN TINDAK PIDANA YANG DILAKUKAN PREMAN DI OBYEK WISATA KOTA PADANG - Suryadi, Arief (Universitas Ekasakti, 2020)
Throughout 2016 to 2018 there were 29 cases of criminal acts committed by thugs in vital tourism objects in the city of Padang. Thug Handling of Tourism Objects in Padang City By Pam Obvit West Sumatra Regional Police is conducted by conducting raids or inspections by officers of the Padang City tourism area. Constraints in Tackling Thugs in Tourism Objects in Padang City By Pam Obvit West Sumatra Regional Police is a factor in human resources / lack of personnel, lack of community participation / management of attractions. Efforts Made by the Directorate of Safeguarding Vital Objects in Overcoming Barriers to Safeguarding Tourism Objects against Thugs in the City of Padang tourist area is to increase Human Resources or the Number of Police Personnel by empowering the local Bhabinkamtibmas, Increasing community participation / management of tourism objects. Optimizing the Role of West Sumatra Regional Police Obvit Pam in the Thugs Repacking in Tourism Objects in Padang City with collaborative efforts between the police and the community through police synergy where both together identify and solve the occurrence of thug problems.